Soziopragmatik von unser bei Rufnamen im Westmitteldeutschen.: Zum Gebrauch sprecherassoziierter Referenzausdrücke - Werth, Alexander (Linguistik Online, 2021)
Speakers of Western Central German dialects frequently use the first person plural form of the possessive article unser with proper names (e. g. us Dietmar ‘our Dietmar’). But conditions of use are so far totally unclear. This paper focuses on form and use of unser with proper names in Moselle Franconian dialects. The findings are based on interviews. They show that unser is primarily used to refer to blood relatives. However, consanguinity is a necessary, but not sufficient, condition for unser. In particular, its use is triggered by social closeness and the assumption of responsibility by the speaker.